Usefulness of the 1H NMR Multisuppression Approach for the Global Characterization of Monovarietal Extra-Virgin Olive Oils - Encarnacion Goicoechea-Oses; Ainhoa Ruiz-Aracama (Foods, 2024)
Extra-virgin olive oil (EVOO) is one of the most appreciated vegetable oils worldwide, but its high price makes it prone to suffer adulteration with lower quality oils. Therefore, it is important to have methodologies able to study EVOO composition as a whole in a simple and fast way, in order to guarantee its quality and safety. For this purpose, in this study, commercial samples of five Spanish olive cultivars (Arbequina, Arroniz, Cornicabra, Hojiblanca, Picual) were studied by Proton Nuclear Magnetic Resonance (1H NMR) spectroscopy, using standard and multisuppression pulses. The aim was to explore the possibility of 1H NMR use to characterize in a single run and in a global way the composition of these monocultivar oils, regarding not only their main components (fatty acids supported on triglycerides) but also minor ones (squalene, sterols, diterpenic wax esters of phytol and geranylgeraniol, phenolic and secoiridoid derivatives, like tyrosol, hydroxytyrosol, oleacein, oleocanthal, and lignans, among others, and aldehydes). The use of univariate and multivariate statistical analyses confirmed the presence of compositional features that were specific to some olive varieties. The Arbequina and Arroniz oils showed the most characteristic features that allowed for clearly differentiating them from the others. In contrast, the discrimination between the Cornicabra, Hojiblanca and Picual oils was not so easily achieved.